Análise da eficácia da vacinação contra hepatite B em pacientes submetidos a transplante de fígado - Rodrigues, Isabela Cristina (2019)
In view of the wide genetic variability and different antigen response capabilities, it is known that no vaccine guarantees full protection, and variations in immune response capacity are expected. Patients with hepatopathies are distinguished from the general population by their inability to respond to antigenic stimuli, disfavoring vaccine protection. Therefore, differentiated vaccination schedules may be required. Purpose: 1. The aim of this study is to analyze the conventional and non-conventional Hepatitis B vaccination schedules for patients who underwent liver transplantion. 2. Suggest possible vaccination schedules against Hepatitis B for liver disease patients in relation to the Child-Turcotte Pugh classification, according to evidence found in the literature. Material and Method: This is a descriptive epidemiological study. It is quantitative and retrospective. It was carried out through secondary data collected from the medical records of patients who underwent liver transplantion in Hospital de Base, in São José do Rio Preto/SP/Brazil from 1998 to 2016. Secondary data were collected from the National Immunization Program Information System (SIPNI) and from internal records of vaccine administration at Hospital de Base/São José do Rio Preto/SP/Brazil or in the municipalities the patients were from. The sample comprised of 177 patients. Patients without vaccine records and HBV-positive patients were excluded. Retransplanted patients were considered only once, and patients with no information regarding the vaccination record and patients without an anti-Hbs examination registry. Results: Data resulted in 72.89% male; 68,67% between 19 and 59 years old (median 52 years); 39.55% cirrhosis diagnosis with associated causes; 23.16% Hepatocarcinoma (CHC); 53.11% classified as Child C; 58.76% Hepatitis C virus (HCV) carriers; 97.18% non-conventional vaccination schedule; seroconvertion in 40% of the patients who completed the conventional vaccination schedule and 36.63% with non-conventional vaccination schedule. The fact the patients were carriers of the HCV was statistically significant regarding the ineffectiveness of anti-HBV vaccine. There were five times more chances not to seroconvert at the end of the vaccination schedule. Conclusion: It is concluded that the conventional and non-conventional vaccination schedules have low seroconversion values in the studied population, with no superiority in relation to the other. Based on a systematic review of the literature in relation to the proposed subject, the vaccination schemes non-conventional in relation to the Child-Turcotte Pugh classification.